Black soybeans protect human keratinocytes from oxidative stress‐induced cell death. Issue 8 (20th October 2018) - Yoon, Young; Lee, Yoon‐Mi; Song, Sooji; Lee, Yu Young; Yeum, Kyung‐Jin
Abstract: Black soybeans are functional foods containing a variety of bioactives such as isoflavones, carotenoids, tocopherols, phenolic acid as well as anthocyanins. Here, we examined whether Cheongja#3 black soybean extract has a protective effect on oxidative stress‐induced cell death in human keratinocytes HaCaT. First, we identified fat‐soluble bioactives in three varieties of soybean extracts (Saedanbaek, Daechan, and Cheongja#3). In particular, black soybean Cheongja#3 had high amounts of lutein than other varieties. We demonstrated that Cheongja#3 extract reduced intracellular reactive oxygen species levels in HaCaT cells. Furthermore, Cheongja#3 protected cells from hydrogen peroxide (H2 O2 )‐induced oxidative stress and triggered cell death determined by cell viabilities and apoptotic caspase activities. Next, we identified the underlying mechanism is due to increased Nrf2 antioxidant system by Cheongja#3, thus increasing the expression of heme oxygenases (HO)‐1. These results indicated that Cheongja#3 soybean extract has protective role against oxidative stress by upregulating the Nrf‐2 antioxidant system in human keratinocyte HaCaT cells. Abstract : In this study, we demonstrated that black soybean "Cheongja#3" had protective effects on HaCaT cells from oxidative stress via upregulation of Nrf2 antioxidant system.